Sex differences in cardiovascular morbidity associated with familial hypercholesterolaemia: A retrospective cohort study of the UK Simon Broome register linked to national hospital records. (December 2020) - Iyen, Barbara; Qureshi, Nadeem; Weng, Stephen; Roderick, Paul; Kai, Joe; Capps, Nigel; Durrington, Paul N.; McDowell, Ian FW.; Soran, Handrean; Neil, Andrew; Humphries, Steve E.
Abstract: Background and aims: The UK Simon Broome (SB) familial hypercholesterolaemia (FH) register previously reported 3-fold higher standardised mortality ratio for cardiovascular disease (CVD) in women compared to men from 2009 to 2015. Here we examined sex differences in CVD morbidity in FH by national linkage of the SB register with Hospital Episode Statistics (HES). Methods: Of 3553 FH individuals in the SB register (aged 20–79 years at registration), 2988 (52.5% women) had linked HES records. Standardised Morbidity Ratios (SMbR) compared to an age and sex-matched UK general practice population were calculated [95% confidence intervals] for first CVD hospitalisation in HES (a composite of coronary heart disease (CHD), myocardial infarction (MI), stable or unstable angina, stroke, TIA, peripheral vascular disease (PVD), heart failure, coronary revascularisation interventions). Results: At registration, men had significantly ( p  < 0.001) higher prevalence of previous CHD (24.8% vs 17.6%), previous MI (13.2% vs 6.3%), and were commenced on lipid-lowering treatment at a younger age than women (37.5 years vs 42.3 years). The SMbR for composite CVD was 6.83 (6.33–7.37) in men and 7.55 (6.99–8.15) in women. In individuals aged 30–50 years, SMbR in women was 50% higher than in men (15.04 [12.98–17.42] vs 10.03 [9.01–11.17]). In individuals >50 years, SMbR was 33% higher in women than men (6.11 [5.57–6.70] vs 4.59 [4.08–5.15]). Conclusions: Excess CVD morbidity due to FH remains markedly elevated in women at all ages, but especially those aged 30–50 years. This highlights the need for earlier diagnosis and optimisation of lipid-lowering risk factor management for all FH patients, with particular attention to young women with FH. Graphical abstract: Image 1 Highlights: Males with familial hypercholesterolaemia (FH) had more cardiovascular disease (CVD) risk factors and were commenced on lipid-lowering therapy at a younger age, than females with FH. Individuals with FH had excess rates of hospitalisations for CVD, compared to the general population of non-FH individuals. Excess CVD morbidity due to FH was higher in women than men aged 30 years and over, but especially in those aged 30–50 years.